Olfactory preference for egg laying on citrus substrates in Drosophila - Dweck, H.; Ebrahim, S.; Kromann, S.; Bown, D.; Hillbur, Y.; Sachse, S.; Hansson, B.; Stensmyr, M. (Elsevier, 2013)
Egg-laying animals, such as insects, ensure thesurvival of their offspring by depositing their eggs in favorableenvironments. To identify suitable oviposition sites, insects,such as the vinegar fly Drosophila melanogaster, assess acomplex range of features. The fly selectively lays eggs in fermentingfruit. However, the precise cues and conditions thattrigger oviposition remain unclear, including whether flies arealso selective for the fruit substrate itself.Results: Here, we demonstrate that flies prefer Citrus fruits asoviposition substrate. Flies detect terpenes characteristic ofthese fruits via a single class of olfactory sensory neurons, expressingodorant receptor Or19a. These neurons are necessaryand sufficient for selective oviposition. In addition, wefind that the Citrus preference is an ancestral trait, presumablyrepresenting an adaptation toward fruits found within thenative African habitat. Moreover, we show that endoparasitoidwasps that parasitize fly larvae are strongly repelled by thesmell of Citrus, as well as by valencene, the primary ligand ofOr19a. Finally, larvae kept in substrates enriched with valencenesuffer a reduced risk of parasitism. Our results demonstrate that a single dedicatedolfactory pathway determines oviposition fruit substratechoice. Moreover, our work suggests that the fly’s fruit preference—reflected in the functional properties of the identifiedneuron population—stem from a need to escape parasitismfrom endoparasitoid wasps.